A study of self‐hardening bainitic cast steel. Issue 9 (14th September 2013) - Zhou, H.; Wu, Z.‐W.; Fu, H.
Abstract Bainitic cast steel is a kind of wear resistant material which has high strength and toughness, and can usually be obtained by isothermal quenching or molybdenum alloying. However, isothermal quenching has lower production efficiency and molybdenum alloying has higher production cost. In this paper, according to the characteristics that manganese and boron elements delayed the pearlitic transformation, the authors developed a new type of self‐hardening bainitic cast steel in which manganese and boron were main alloy elements and a small amount of titanium, nitrogen, calcium, barium and yttrium elements were also added in the steel that could refine and purify the solidification structure of steel. On this basis, the author studied the effect of tempering treatment on microstructures, mechanical properties and wear resistance of bainitic cast steel. The results showed that impact toughness of bainitic cast steel increased ceaselessly with the increase of tempering temperature, and there was tempering brittleness while tempering from 450°C–500°C. Moreover, the hardness of bainitic cast steel decreased with the increase of tempering temperature, and hardness decreased slowly and maintained at 55HRC or above when tempering temperature was lower than 300°C. Under the condition of two‐body pin‐on‐disc wear, the wear resistance of bainitic cast steel decreased with the increase of tempering temperature, but bainitic cast steel tempering at 300°C had excellent wear resistance in the condition of impact wear. In the practical use, the bucket teeth of excavator and the hammer of crusher making from self‐hardening bainitic cast steel were safe and reliable, and their service life were increased by 120–150% than Hadfield manganese steel.